Analisis Kepuasan Pengguna Aplikasi Bibit Robo Advisor Investasi Reksadana, SBN, Obligasi, dan Saham Menggunakan Model ISO 25010 - Apriana, Doha; Jatnika, Ihsan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The Bibit application is one of the mutual fund applications in Indonesia with the fastest acceptance rate in Indonesia. The app was launched to the public in 2019. The number of users of this application exceeds the number of users of other mutual fund applications that have existed before. What factors cause the Bibit application to get a large number of users, can be known through a study on user satisfaction. This study was conducted with the aim of analyzing user satisfaction using ISO 25010. The characteristics to be analyzed include Functional Suitability, Performance efficiency, usability and maintainability. Data collection was carried out through questionnaires, and data drying using a Likert scale. This study also uses the Analytical Hierarchical Process (AHP) method to find out what factors are considered important by users. The results of the study show that the factors that are considered important by users are functional suitability, performance efficiency, usability and maintainability. The results of the study also show that overall the Bibit application is in the good category.